Risk Assessment and Mitigation Strategy in The Halal Food Supply Chain in The Covid-19 Pandemic - Hana Catur Wahyuni; Boy Isma Putra; Puspista Handayani; Wafika Urfa Maulidah (Jurnal Ilmiah Teknik Industri, 2021)
Halal is mandatory for Muslims in choosing food. During the Covid-19 pandemic, there were changes in the food supply chain system, and there was a risk of changing the status of halal to non-halal due to various sources. The research objectives are to identify halal risk activities in the supply chain, determine risk priorities and develop mitigation strategies. A case study was conducted at a fish cracker company in Sidoarjo, East Java. Data processing was performed using the FMEA method. The results showed 26 risky activities in the fish cracker supply chain, consisting of 9 risks from suppliers, 7 risks from processes, and 10 risks from distributors. The highest risk is in the process of sending crackers from the company to the distributor. A mitigation strategy is prepared by involving the government, suppliers, companies, and distributors. The formulation of a mitigation strategy is focused on the aspects of technology, human resources, and infrastructure.